Studi Kuantitas Air Buangan Kampus Universitas Andalas Limau Manis Padang - Puti Sri Komala; Yenni Ruslinda; Juwita Zurienra (Jurnal Serambi Engineering, 2020)
In this study, the quantity of wastewater from the existing facilities at the Andalas University Campus was carried out. The measured wastewater consists of grey water, black water, and specific wastewater. The wastewater was classified based on its activities, namely dormitories, lecture room, student facilities, offices, religious facilities, cafeterias, sports facilities, laboratories, and campus bus pools. The sampling method used was the bucket method. Grey water sampling was carried out on regular days (Monday-Thursday), worship days (Friday), and holidays (Saturday and Sunday), while specific wastewater and black water were measured on regular days. Peak hours occur at 12.00-14.00 except in the dormitory at 06.00-08.00 and cafeteria at 10.00-11.00. The peak factor of used water ranges from 1.56 to 3.13. From the measurement results obtained the wastewater from dormitory wastewater of 212.8 m3/day; lecture building 491 m3/day; student facilities 32.4 m3/day; offices 245.4 m3/day; worship 50.4 m3/day; cafeteria 109.2 m3/day; sports facilities 8.7 m3/day; laboratory 282 m3/day; corral 27 m3/day; and pool bus 34.7 m3/day respectively. The total wastewater from Unand Limau Manis Campus is 1,439.6 m3/day. The wastewater composition consists of, grey water 812.3 m3/day (52.67%), specific wastewater 343.8 m3/day (23.45%) and 337.5 m3/day (23.88%) black water.